2018
DOI: 10.1177/0018726718809158
|View full text |Cite
|
Sign up to set email alerts
|

Gender gaps at the top: Does board composition affect executive compensation?

Abstract: Will adding women to the board of directors reduce firm gender pay disparities? Our research suggests ‘no’ … and ‘yes.’ It is not a matter of simply adding more women to the board or integrating women into key board committees that moves the needle. If firms really want to stimulate change through board diversity, then they need to empower female directors and place them in key leadership roles. We find that women’s integration on the board of directors and on the compensation committee has no significant impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 77 publications
2
57
1
Order By: Relevance
“…In general, the issue addressed in most of the scientific articles that deal with this subject is whether the presence of women in boards of directors is associated with improved company performance [20], which is measured by financial results [21], the company's level of debt [22] and corporate social responsibility [23]. Other authors have studied the subject from different perspectives, including: the gender pay gap [24], work-life balance [25] and gender quotas [26]. In order to understand the main subject of study and pinpoint noteworthy articles from the selected literature, three time periods have been identified: the first period spans from 1994 to 2005, the second period from 2006 to 2012, and the third period from 2013 to 2020.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the issue addressed in most of the scientific articles that deal with this subject is whether the presence of women in boards of directors is associated with improved company performance [20], which is measured by financial results [21], the company's level of debt [22] and corporate social responsibility [23]. Other authors have studied the subject from different perspectives, including: the gender pay gap [24], work-life balance [25] and gender quotas [26]. In order to understand the main subject of study and pinpoint noteworthy articles from the selected literature, three time periods have been identified: the first period spans from 1994 to 2005, the second period from 2006 to 2012, and the third period from 2013 to 2020.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their research results are clear: the stock market would react positively to the announcement of women being appointed to boards of directors, as it was believed that they would provide added value, reaffirming that the approved legislation made sense and contributed to the main objective. Other articles analyze the differences between men and women in order to try to explain why the results may be different when the person directing a company is either male or female [19,24,28]. Along these lines, academics such as [2] demonstrate in their studies that women are less prone to taking risks, have different priorities and are less concerned with power.…”
Section: Second Period (2006-2012)mentioning
confidence: 99%
“…If firms really attempt to stimulate change in executive gender pay gap through board diversity, then they need to empower women directors or executives and place them in the key leadership positions. It is found that females' integration on the board of directors and on the compensation committee has no significant impact on lessening the executive gender compensation gap (Cook et al, 2019). However, when females affect compensation decisions through the role as the chair of the compensation committee, the executive gender compensation gap is nearly diminished.…”
Section: Impact Mechanisms Of Female Executives On Pay Gapmentioning
confidence: 94%
“…A large-scale meta-analysis revealed that the gender gap for performance evaluations and rewards (e.g., pay and promotion) was smaller in industries where women were more strongly represented at the upper echelons (e.g., executive and senior managerial levels; Joshi et al, 2015). Similarly, Cook et al (2019) found that when female board members held positions of greater influence (i.e., chaired the compensation committee), the gender pay gap among the top management team was reduced.…”
Section: The Moderating Role Of Board and Compensation Committee Gender Compositionmentioning
confidence: 99%
“…To provide further insight as to why female CEOs receive lower compensation relative to male CEOs for external board memberships, we conducted supplemental analyses. Specifically, some prior research revealed that female representation on the board may not be sufficient to ensure equitable compensation, but rather these women need to be influential (e.g., Cook et al, 2019). In other words, perhaps if T A B L E 6 Supplemental analysis: The moderating impact of female board power female directors generally hold powerful roles on the board, reflecting their position at the table is legitimate and merited rather than as symbolic tokens, this may mitigate the gendered effect of CEO external board memberships on CEO pay.…”
Section: Supplemental Analysesmentioning
confidence: 99%